Motivations for farmers’ participation in agri-environmental scheme in the EU, literature review - Podruzsik Szilárd; Fertő Imre (Open Agriculture)
Agri-environmental schemes (AESs) play a pivotal role in aligning agricultural practices with environmental objectives, promoting sustainable land management, and conserving biodiversity. This article presents a comprehensive synthesis of recent advancements in AES research within the European Union context, focusing on ecological, economic, and socio-political dimensions. Through a systematic review of literature published since 2013, we identify emerging trends, gaps, and research priorities, providing novel insights into AES effectiveness. We examine the factors that influence participation in AES such as biodiversity, habitat fragmentation, and agricultural ecosystem services. We also explore the economic factors influencing farmer participation, including financial incentives, income stability, and cost–benefit analysis. Furthermore, we investigate the socio-political dimensions of AES, including institutional frameworks, stakeholder engagement, and the role of trust in programme implementation. Key findings highlight the need for adaptive management strategies, incentive structures aligned with environmental objectives, and inclusive governance mechanisms to enhance AES effectiveness. Our research underscores the importance of context-specific approaches that account for farm characteristics, socio-economic factors, and institutional arrangements. Practical implications for policymakers, practitioners, and stakeholders are discussed, emphasizing the importance of evidence-based policymaking and iterative learning in promoting sustainable agriculture and environmental conservation.